A microeconomic explanation of the EPK paradox - Wolfgang Karl Härdle; Volker Krätschmer; Rouslan A. Moro (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2009)
Supported by several recent investigations the empirical pricing kernel paradox might be considered as a stylized fact. In Chabi-Yo et al. (2008) simulation studies have been presented which suggest that this paradox might be caused by regime switching of stock prices in financial markets. Alternatively, we want to emphasize a microeconomic view. Based on an economic model with state dependent utilities for the financial investors we succeed in explaining the paradox by changes of the risk attitudes. Theoretically, the change behaviour is compressed by the pricing kernels. As a starting point for empirical insights we shall develop and investigate inverse problems in terms of data fits for estimated basic values of the pricing kernel.
Keywords: D01; D58; C02; G13; 330; Pricing kernel; representative agent; empirical pricing kernel; epk paradox; state dependent utilities; switching points; Börsenkurs; Anlageverhalten; Risikopräferenz; Erwartungsnutzen; Theorie